x(x)-18x+74=0

Simple and best practice solution for x(x)-18x+74=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x)-18x+74=0 equation:


Simplifying
x(x) + -18x + 74 = 0

Multiply x * x
x2 + -18x + 74 = 0

Reorder the terms:
74 + -18x + x2 = 0

Solving
74 + -18x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-74' to each side of the equation.
74 + -18x + -74 + x2 = 0 + -74

Reorder the terms:
74 + -74 + -18x + x2 = 0 + -74

Combine like terms: 74 + -74 = 0
0 + -18x + x2 = 0 + -74
-18x + x2 = 0 + -74

Combine like terms: 0 + -74 = -74
-18x + x2 = -74

The x term is -18x.  Take half its coefficient (-9).
Square it (81) and add it to both sides.

Add '81' to each side of the equation.
-18x + 81 + x2 = -74 + 81

Reorder the terms:
81 + -18x + x2 = -74 + 81

Combine like terms: -74 + 81 = 7
81 + -18x + x2 = 7

Factor a perfect square on the left side:
(x + -9)(x + -9) = 7

Calculate the square root of the right side: 2.645751311

Break this problem into two subproblems by setting 
(x + -9) equal to 2.645751311 and -2.645751311.

Subproblem 1

x + -9 = 2.645751311 Simplifying x + -9 = 2.645751311 Reorder the terms: -9 + x = 2.645751311 Solving -9 + x = 2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 2.645751311 + 9 Combine like terms: -9 + 9 = 0 0 + x = 2.645751311 + 9 x = 2.645751311 + 9 Combine like terms: 2.645751311 + 9 = 11.645751311 x = 11.645751311 Simplifying x = 11.645751311

Subproblem 2

x + -9 = -2.645751311 Simplifying x + -9 = -2.645751311 Reorder the terms: -9 + x = -2.645751311 Solving -9 + x = -2.645751311 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = -2.645751311 + 9 Combine like terms: -9 + 9 = 0 0 + x = -2.645751311 + 9 x = -2.645751311 + 9 Combine like terms: -2.645751311 + 9 = 6.354248689 x = 6.354248689 Simplifying x = 6.354248689

Solution

The solution to the problem is based on the solutions from the subproblems. x = {11.645751311, 6.354248689}

See similar equations:

| x^2+24x+16=0 | | x^2-20x-1=7 | | p(p)+6r+8=0 | | 75x+41+39x=(-17x) | | p(p)+6p+8=0 | | =6x+12x+x | | 3x+40+2x-10=180 | | 3z-4=z+6 | | 4x+5=89 | | y(y)-6y-7=0 | | -8x-60=4 | | 2x-36=-44 | | 14x-64=90 | | 20x-3=71 | | x^2+12x=-2 | | -52x-18=86 | | x^3+3x^2-2x=0 | | x(x)+7x+6=0 | | x(x)-2x+1=0 | | -4x+17=86 | | 4p(p)+8p=0 | | 10x-30=-80 | | (2b+1)(2b+1)=25 | | -5x+6y=69 | | 15x+17=-73 | | -6x-63=-75 | | -6-63=-75 | | x^3-6x-9=0 | | 3(x^2)+32x+45= | | x(x)-x-20=0 | | 30(x^2)+37x+10= | | 16=4(x-5)2 |

Equations solver categories